Hubungan Mekanisme Corporate Governance dan Kinerja Keuangan Bank Pembiayaan Rakyat Syariah - Eriza Mayang Kusuma; Supatmi Supatmi (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
This study aims to find the empirical evidence about the correlation of corporate governance with the financial performance of Islamic rural bank (Bank Pembiayaan Rakyat Syariah/BPRS). The samples are 97 Islamic rural banks in Indonesia, which published financial statements during 2011-2012. The corporate governance mechanism is measured by independent board, board of directors, managerial and institutional ownership. Financial performance is measured by financial ratios, i.e. NPF, CAR, FDR, ROA and ROE. The hypotheses are tested using Chi square test. This study showed that the board of director was positively related to the ability to cope with the level of non performing loans (NPF), both managerial and institutional ownership was positively related to the return on assets and equity (ROA and ROE).